2017
DOI: 10.1074/jbc.m117.786582
|View full text |Cite
|
Sign up to set email alerts
|

Short-term starvation is a strategy to unravel the cellular capacity of oxidizing specific exogenous/endogenous substrates in mitochondria

Abstract: Mitochondrial oxidation of nutrients is tightly regulated in response to the cellular environment and changes in energy demands. studies evaluating the mitochondrial capacity of oxidizing different substrates are important for understanding metabolic shifts in physiological adaptations and pathological conditions, but may be influenced by the nutrients present in the culture medium or by the utilization of endogenous stores. One such influence is exemplified by the Crabtree effect (the glucose-mediated inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…The reduction of mitochondrial NADH would impair mitochondrial respiratory capacity, as predicted by the model and measured by experiments. The link between glycolysis and maximal respiration has been previously reported—inhibition of glycolysis by glucose restriction or pharmacological inhibitors can impair respiration generally (Clerc & Polster, ; Pike Winer & Wu, ; Zeidler et al, ), and maximal respiration specifically (Gouarne et al, ; Tan, Xiao, Li, Zeng, & Yin, )—further validating the strong link between glucose metabolism and mitochondrial activity.…”
Section: Discussionsupporting
confidence: 57%
“…The reduction of mitochondrial NADH would impair mitochondrial respiratory capacity, as predicted by the model and measured by experiments. The link between glycolysis and maximal respiration has been previously reported—inhibition of glycolysis by glucose restriction or pharmacological inhibitors can impair respiration generally (Clerc & Polster, ; Pike Winer & Wu, ; Zeidler et al, ), and maximal respiration specifically (Gouarne et al, ; Tan, Xiao, Li, Zeng, & Yin, )—further validating the strong link between glucose metabolism and mitochondrial activity.…”
Section: Discussionsupporting
confidence: 57%
“…In order to evaluate the use of different substrates by cells, we submitted the cells to a short-term nutrient deprivation protocol, which consisted of cell incubation for 1 h in restricted medium (RM; DMEM [Dulbecco’s modified Eagle’s medium] without glucose, glutamine, and sodium pyruvate) without fetal bovine serum (FBS), before carrying out the experiments. This protocol makes the cells prone to use the chosen substrate without loss of cellular viability, overcoming the influence of the nutrients present in the culture medium ( 26 ). Huh7 cells were subjected to mock infection or DENV infection for 24 h, and the OCR was measured when the only substrate added after nutrient deprivation was palmitate, glutamine, glucose, or pyruvate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used short-term cellular starvation as a strategy to prevent the possibility that the nutrients already present in the culture medium as well as the endogenous substrates would influence the observation of the metabolic alterations induced by infection. This experimental approach was recently developed by our group ( 26 ) and allowed us to evaluate the contribution of fatty acids, glutamine, glucose, and pyruvate to mitochondrial oxygen consumption during DENV infection. Interestingly, we found that DENV infection inhibited the Crabtree effect, resulting in an increase in the cellular capacity of metabolizing glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid possible interferences with other metabolites from culture media and serum, in this work, we performed the short-time experiments in very restrictive conditions, although it should be taken into account that other metabolites may also be present in an individual. Thus, this kind of methodological approximation allows for the determination of the short-time preference of a metabolic substrate in these cells when only these fuels are present at physiological concentration after a fasted period [12,13]. Combining long-and short-term experiments covers different possible scenarios, such as the short-term response of the cells to a drastic nutritional change (their immediate fuel preference) and the long-term consequence of that change (their ability to adapt to a different nutritional condition).…”
Section: Introductionmentioning
confidence: 99%